Design of a solar power plant system for micro, small, medium enterprise uses PVSyst 7.1 as a renewable energy alternative source in remote areas. Issue 1 (January 2022) - Windarta, J; Handoko, S; Sukmadi, T; Nafadinanto, K; Muqtasida, S; Halim, C
Abstract: PLN electricity distribution goal for remote areas is not achieved yet so that alternative sources are needed, for instance, solar power plants. The purpose of this study is to design and analyze the solar power plant potential with an off-grid system that is used to supply SME electricity in electrical and economic terms. The daily load data profile used by SME is 1.8 kWh. This study uses PVSyst 7.0 software as design tool simulation system and RETscreen software as an economic analysis tool simulation. The result of this solar power plant system design requires a 700Wp solar module, 24V 160Ah battery, 24V 1000W inverter, and SCC 30A. With the planned system design, the electrical energy generated in the PVSyst simulation in one day is estimated to reach 2 kWh with the use of 50% Deep of Discharge battery capacity considering the length of battery life span. To return the investment cost of this solar power plant system, PLN electricity cost needed is Rp 2, 664.